2010
DOI: 10.1007/s00430-010-0182-x
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of experimental influenza virus infection with pyrrolidine dithiocarbamate

Abstract: The search for new antiviral strategies to treat influenza A virus (IAV) infections is one major international health care activity. Hereby, the IAV-caused misuse of cellular nuclear factor kappa B (NF-κB) signaling pathways in infected cells represents one target for antiviral therapy. In the present study, pyrrolidine dithiocarbamate (PDTC), which is known as an antioxidant and as an inhibitor of IAV-induced NF-κB activation, was studied in vivo. After the antiviral activity of PDTC was confirmed in MDCK cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…PDTC, an antioxidant and radical scavenger, has been shown to possesses antiviral activity against CVB3, influenza virus, rhinovirus, and herpes simplex virus (Krenn et al, 2005;Lanke et al, 2007;Qiu et al, 2013;Si et al, 2005;Wiesener et al, 2011). In this study, we found that PDTC could inhibit viral RNA synthesis, viral protein expression, and the overall virus yield of EV71.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…PDTC, an antioxidant and radical scavenger, has been shown to possesses antiviral activity against CVB3, influenza virus, rhinovirus, and herpes simplex virus (Krenn et al, 2005;Lanke et al, 2007;Qiu et al, 2013;Si et al, 2005;Wiesener et al, 2011). In this study, we found that PDTC could inhibit viral RNA synthesis, viral protein expression, and the overall virus yield of EV71.…”
Section: Discussionmentioning
confidence: 64%
“…Pyrrolidine dithiocarbamate (PDTC) is a synthetic compound, which is largely used as antioxidant or nuclear factor kappa B (NF-B) inhibitor (Morais et al, 2010;Wiesener et al, 2011;Yucel et al, 2013). Previous studies have shown that PDTC could inhibit the replication of coxsackievirus B3 (CVB3), rhinovirus, influenza virus, and herpes simplex virus (Krenn et al, 2005;Qiu et al, 2013;Si et al, 2005;Uchide and Ohyama, 2003;Uchide et al, 2002;Wiesener et al, 2011), while the precise mechanism involved in the antiviral activity of PDTC has not been elucidated.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Three other NF‐ κ B inhibitors, pyrrolidine dithiocarbamate , SC75741 , and Bay 11–7082 (Fig. C), were reported to significantly decrease influenza virus‐induced disease in mice …”
Section: Strategies To Interfere With the Influenza Virus Polymerasementioning
confidence: 98%
“…Thus, inhibitors of NF-κB may have a two-pronged beneficial effect in influenza: they will inhibit the virus directly and will also moderate the systemic inflammation. This has been shown in cell culture and mice [84-86], but specific and controlled studies in patients with influenza still need to be done. Nonetheless, the prospects of an anti-inflammatory therapy of influenza are real, because some anti-NF-κB drugs, such as acetyl salicylate (aspirin) are routinely sold in stores without prescription and widely used by the general public for many years without major side effects.…”
Section: Reviewmentioning
confidence: 99%